Effect of Extracurricular and Co-Curricular Activities on Students’ Development in Higher Education - Nandita Mishra; Aithal P. S. (International Journal of Management, Technology and Social Sciences (IJMTS), 2023)
Purpose: The current mandate of the New Education Policy 2020, is to prepare students for the evolving industry practices and skills. Academic qualifications alone through the curriculum are not sufficient to adapt to the VUCA world. Extracurricular activities coupled with co-curricular activities can enforce all round personality development of students. Extracurricular activities make the learner mentally agile, participative, responsive, confident, and independent. An illustration through a case in point enables understanding of the importance of extracurricular activities and how they prove to be beneficial for learners in the higher education system. Approach: Data is obtained through the survey method to study the impact of extracurricular activities. The paper is based on analysis of selected relevant papers and articles related to extracurricular activities. The authors have attempted to incorporate the analysis of primary data to establish the role of extracurricular and co-curricular activities. Result: The analysis shows that both extracurricular and curricular activities contribute towards confidence building, along with the development of knowledge, skills, and attitude Value: With the current mandate of Skill India mission and developing youth for Industry 4.0, to match the skills required in the ever-changing requirement, this paper will contribute to the understanding, of how the skills can be developed for the learners in Higher Education. Type of Paper: Exploratory Qualitative paper